Perencanaan Kebutuhan Alat Gali-Muat dan Angkut dengan Kapasitas Ore Getting 200 m3/jam pada Rencana Penambangan PT Timah (Persero) Tbk - Rajandra Nurhadi; Guskarnali Guskarnali; Irvani Irvani (MINERAL, 2018)
PT Timah (Persero) Tbk is a company engaged in mining especially tin. Tin is one of the most important deposits in the development of world technology. PT Timah (Persero) Tbk has an important role in the procurement of tin in the world. In mining, the mine planning stage is very important before the exploitation stage. At the planning stage of a mine will be planned in such a way as to obtain optimal results. One of the stages of mine planning is the planning of the required load equipment and haul equipment. PT Timah (Persero) Tbk plans to open a mine with open pit system that is using mechanical equipment in Mining Permit Area of West Bangka Regency, Bangka Belitung Islands Province. The mine plan has an ore-gain capacity of 200 m3/hour, requiring the planning of load and haul equipment to meet the ore getting capacity and stripping of overburden and haul geometry in general. Based on the factors that exist in the mine, the load equipment used is the excavator and haul equipment used is Articulared Dumpt Truck. By taking the cycle time as a reference and then converted by the distance of overburden stripping and ore getting activity every year, then can be known the productivity of equipment and the amount of equipment required each activity every year. The number of equipment required is at least 1 load equipment and 4 haul equipment, while the most are 4 load equipment and 13 haul equipment. The geometry of the haul road based on the specification of the haul equipment at the location of the plan has the width of the haul road on a 12 meter straight road, the haul road width at 21 meters, and the 9,1 meter bend radius